Franceso Jovino and A Brief Discussion of Catholic Meditation: A Glimpse into the Spread of Catholicism in Gansu Province During the Mid-Qing Dynasty - GUO Ting, (Journal of Research for Christianity in China (JRCC), 2025)
This paper will discuss A Brief Discussion of Catholic Meditation, a book written by Reformed Franciscan missionary Francesco Jovino (1688-1737) during the time of Qianlong and Yongzheng’s imperial edicts against Christianity in 1717 and 1724. We will first introduce the meditative tradition of Francisicanism, then sketch the historical and social context of Jovino’s mission in Gansu. This context will allow a preliminary analysis of the theology of this book. By doing so, we hope to shed light on the Catholic missions in Gansu Province in mid-Qing period, and show how some missionaries responded to the edicts of persecution by promoting the spiritual traditions of Franciscanism.